Effect of Betel Leaf Decoction against Ectoparasites Intensity of Monogenea - Kalista Moolulungo; Rully Tuiyo; Juliana Juliana (Faculty of Fishery and Marine Sciences - Universitas Negeri Gorontalo, 2019)
This study aims to determine the effect of the decoction of betel leaf (Piper betle Linn) in the prevention of parasitic Cichlidogyrus sp on tilapia fish (Oreochromis niloticus) and calculate the intensity level of Cichlidogyrus sp parasites on the gills organ of tilapia. The research method using experimental methods and data processing is done descriptively. Immersion of tilapia in betel leaf (Piper betle Linn) decoction has no effect on the level of intensity of monogenea ectoparasite Cichlidogyrus sp. The level of intensity of the parasite at the highest in treatment A is 2.24 and the lowest in treatment D is 1.58 count/individual. Water quality parameter during the study is still in the proper conditions for the life of tilapia. Keywords: Betel leaf; ectoparasites; monogenea; tilapia; Oreochromis niloticus